The D0 Run IIb luminosity measurement - Casey, B; Corcoran, M; Devaughan, K; Enari, Y; Gallas, E; Katsanos, I; Linnemann, J; Orduna, J; Partridge, R; Prewitt, M; Schellman, H; Snow, G; et al. (2013)
An assessment of the recorded integrated luminosity is presented for data collected with the D0 detector at the Fermilab Tevatron Collider from June 2006 to September 2011 (Run IIb). In addition, a measurement of the effective cross-section for inelastic interactions, also referred to as the luminosity constant, is reported. This measurement incorporates new features that lead to a substantial improvement in the precision of the result. A luminosity constant of σLM=48.3±1.9±0.6mb is obtained, where the first uncertainty is due to the accuracy of the inelastic cross-section used by both CDF and D0, and the second uncertainty is due to D0 sources. The recorded luminosity for the highest ET jet trigger is Lrec=9. 2±0.4fb-1, with a relative uncertainty of 4.3%. © 2012 Elsevier B.V.